Cross Infection in Dentistry and the Dental Aerosols - A Potential Health Hazard - Angabeen Anjum; Mervyn Hosein; Saima AkramButt; Fakhuruddin (ziauddin University, 2020)
Many hazards are often associated with different occupations and known as occupational hazards. Dentistry is also one of those professions having many occupational risks. Such hazards are broadly categorized into chemical, biological, physical, mechanical and psychological factors. Cross infection is one of such hazards faced by the health care providers' particularly dental workers. Cross infection is the transmission of infectious agents between patient and staff in clinical environment. Control of cross infection has remained the major concern of the dental community for decades. Various vectors are involved in cross infections in Dentistry including patients, environment (water, air), instruments etc. Particularly among the environmental factors, airborne route is one of the major routes of cross contamination and so aerosols produced in dental environment carry greatest pathogenic potential. Production of aerosols and splatters occur because of many procedures carried out in mouth including crown preparation, ultrasonic scaling, caries excavation etc. Patients, dental instruments and dental unit waterlines (DUWL) are the important sources of contaminated aerosol production in dental operatory. Use of personal Protective equipments, regular use of pre-procedural mouth rinses and high evacuation devices are few of the suggested methods to reduce risk of cross contamination especially through aerosols and splatters in the dental offices. The related articles were searched through PubMed and Google Scholar.